Twelve-month follow-up of dexamethasone implants for macular edema from various diseases in vitrectomized and nonvitrectomized eyes - Novais, Eduardo A. [UNIFESP] (2016)
Purpose. To evaluate the best-corrected visual acuity (BCVA), central retinal thickness (CRT), and the number of dexamethasone implants needed to treat cystoid macular edema (CME) from various etiologies over 12 months in vitrectomized and nonvitrectomized eyes. Methods. This multicenter retrospective cohort study included 112 patients with CME secondary to retinal diseases treated pro re nata (PRN) with a 0.7 mg intravitreal dexamethasone implant for 12 months. The BCVA, CRT, adverse events, safety data, and number of implants were recorded. Results. Vitrectomized and nonvitrectomized eyes received means of three implants and one implant, respectively, over 12 months (p < 0.001). The mean BCVA of all patients improved from 0.13 at baseline to 0.33 (p < 0.001) 12 months after one (p = 0.001), two (p = 0.041), and three (p < 0.001) implants but not four implants (p = 0.068). The mean baseline CRT decreased significantly (p < 0.001) from 463 to 254 microns after 12 months with one (p < 0.001), two (p = 0.002), and three (p = 0.001) implants but not with four implants (p = 0.114). The anatomic and functional outcomes were not significantly different between vitrectomized and nonvitrectomized eyes. Increased IOP was the most common adverse event (23.2%). Conclusions. Dexamethasone implant administered PRN improved VA and decreased CRT in CME, with possible long-term clinically relevant benefits for treating CME from various etiologies. Vitrectomized eyes needed more implants compared with nonvitrectomized eyes.